Performance and Exit Flow Characteristics of Mixed-Flow Turbines - C. Arcoumanis; R. F. Martinez-Botas; J. M. Nouri; C. C. Su (International Journal of Rotating Machinery)
The performance and exit flow characteristics of two mixed-flow turbines have been investigated under steady-state conditions. The two rotors differ mainly in their inlet angle geometry, one has a nominal constant incidence (rotor B) and the other has a constant blade angle (rotor C), but also in the number of blades. The results showed that the overall peak efficiency of rotor C is higher than that of rotor B. Two different volutes were also used for the tests, differing in their cross-sectional area, which confirm that the new larger area volute turbine has a higher efficiency than the old one, particularly at lower speeds, and a fairly uniform variation with velocity ratio.